Environmental activism and the media the politics of protest - Newlands, Maxine (New York Peter Lang, 2018)
"For more than 40 years politicians, activists, advocates and individuals have been seeking ways to solve the problem of climate change. Governments and the United Nations have taken an economic path. Others seek solutions in the equality of climate justice. Taking the step from green consumer to the streets at climate summits, protest camps and direct action recasts activists as everything from tree huggers, to domestic extremists and ecoterrorists. Political policing and new legislation increasingly criminalized environmental activism, supported by media reporting that recasts environmental activism as actions to be feared. Why this has happened and how activist have learnt to circumvented the media's recasting is the story of this book. From media movements to persuade the moveable middle, high court challenges, and gatekeeping, activists have found ways to challenge media and political discourse. The book identifies four key areas to tie together diverse sets of green governmentality, traditional media discourse and activism. (1) Environmental Governance and green governmentality; (2) historical media discourse; (3) alternative communication infrastructures and (4) local to the global. Using data from 50 interviews, archival research and non-participatory observation from environmental activists from the UK, USA and Australia, this book will show why protest is important in democratic political participation. From activists to slacktivist, Environmental Activism and the Media: the Politics of Protest is for those with an interest in cultural, social and political studies, democratic processes, climate and social justice, governmentality and studying environmental politics, human geography, communication, and sustainability"--Provided by publisher.
Media governance, ecoactivism and the traditional media -- Environmental governance: the role of environmental activism in contentious politics -- Recasting environmental activism as criminal dissent: soft power, political policing and the media -- Don't glue yourself to the prime minister!: millennial media movements and alternative activists communication strategies -- Activism is more than "hits" and "likes": social media strategies and the moveable middle -- Heterotopias: retaining power in the space of protest -- Politics of protest: environmental activism in a heated world.
Includes bibliographical references and index.
Keywords: Mass media and the environment -- Australia; Mass media and the environment -- Great Britain; Mass media and the environment -- United States; Environmentalism -- Australia; Environmentalism -- Great Britain; Environmentalism -- United States